Cortisol Response to Psychosocial Stress in Chinese Early Puberty Girls: Possible Role of Depressive Symptoms. (4th June 2015) - Sun, Ying; Deng, Fang; Liu, Yang; Tao, Fang-Biao
Abstract : Objective . The present study aimed at investigating unique patterns of salivary cortisol reactivity and recovery in response to a social stressor among girls with early puberty and exploring possible role of depressive symptom in this association. Design . Case-control study. Patients . Fifty-six girls with early puberty and age- and body mass index- (BMI-) matched normal puberty controls ( n = 56 ) were selected. Measurements . Salivary cortisol was measured in response to the Groningen Social Stress Test for Children. Results . Girls with early puberty had higher cortisol concentration at the end of the GSST (C3), cortisol concentration 20 min after the end of the GSST (C4), and AUC increment (AUCi) compared to non-early puberty girls. Depressive symptoms correlated with blunted HPA reactivity among girls with early puberty. Conclusion . This study demonstrated the disturbance effect of objectively examined early pubertal timing on HPA axis responses. It also suggested that stress reactivity might be blunted for individuals with depressive symptoms.